Improving Legal Regulation in the Field of Reducing Greenhouse Gas Emissions in the Russian Federation - E. V. Kotova (Теоретическая и прикладная юриспруденция)
Carbon regulation in Russia is at the stage of formation, which requires the development of an integrated approach based on the principles of sustainable development, taking into account international experience. With an understanding of the importance of the problem of climate change for the future of the country and the entire planet, as well as in fulfillment of international obligations, Russia has adopted a number of measures to nationally regulate greenhouse gas emissions reduction, as well as other mechanisms that help slow down global changes.The purpose of this article is to develop comprehensive legal solutions to optimize the system of regulatory legal regulation of issues of reducing greenhouse gas emissions. The research problem lies in the formation of such mechanisms of state climate regulation, which, on the one hand, will contribute to achieving the goals of reducing greenhouse gas emissions set by Russia, and on the other hand, will correspond to the current foreign policy challenges, the ambiguous geopolitical and difficult economic situation that affect public policy, the business community and the global interaction on climate issues.